Green Awareness, Brand Image dan Niat Pembelian - Alamsyah, Doni Purnama; Hadiyanti, Dian (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2017)
The purpose of this study to know the factors that determine the intention of purchasing green product by considering green awareness and brand image factors through the testing of causality and mediation. The study was conducted in one of the companies that produce environmentally friendly products namely Pronaturlite. Number of respondents as many as 705 consumers in the city of Bandung. The analytical technique used is path analysis through SmartPLS. The results of this study confirm the results of previous studies that show that green awareness and brand image affect the purchase intention, green awareness affects the brand image. In addition, brand image can mediate the relationship of green awareness and purchase intention. This study has implications that companies producing green products are advised to control green awareness and brand image in order to increase consumer purchase intention.